Pengaruh Kecerdasan Emosional, Perilaku Belajar, Dan Motivasi Terhadap Tingkat Pemahaman Akuntansi Dasar Mahasiswa Program Studi Akuntansi - Widya Denisa; Yayuk Nurjanah (JAS-PT (Jurnal Analisis Sistem Pendidikan Tinggi Indonesia), 2021)
Accounting students are required to have an understanding of basic accounting skills as well as good and correct accounting concepts such as studying the Introduction to Accounting courses which are given as initial guidelines in exploring other levels of accounting sciences and to support their success in entering the world of work, especially in the accounting field. However, there are still many students who are not able to improve their achievements in the application of basic accounting science, the problem faced by students is the inability to clearly understand what they have learned and unable to solve problems related to the subject. This can happen due to various factors, such as the style of the lecturer in teaching, the lecture system that is not correct, learning behavior, motivation and mental disturbance of students when participating in learning. A student is expected to be able to control and study himself in terms of regulating emotions, motivation to study accounting diligently, and social interaction with his environment. If students are able to control their emotions coupled with good and regular learning patterns and an unyielding attitude in the face of every failure or problem, students will find it easier to make the right decisions, easy to understand what they are learning, especially basic accounting material and to improve achievement and grades. the good one. The purpose of this study was to determine the effect of emotional intelligence, learning behavior, and motivation on the level of basic accounting understanding of accounting study program students. This type of research is quantitative research. The research subjects used by the author are students of the Accounting Study Program at the Bogor Unity Institute of Business and Informatics with a population of 1,302 people, consisting of 988 Bachelor of Accounting and 314 Diploma of Accounting. The data collection in this study used primary data with research instruments using a questionnaire via Google Form which was distributed directly to the research sample through social media as measured by a Likert scale. The sample selection technique used purposive sampling with sampling based on criteria that had been determined by the author with the sampling unit through the Slovin formula totaling 306. The data analysis technique was carried out using Multiple Linear Regression Analysis with the help of SPSS (Statistical Product and Service Solutions) Version 16. The results showed that partially (1) emotional intelligence had a significant negative effect on the level of basic accounting understanding, (2) learning behavior had no significant effect on the level of basic accounting understanding, and (3) motivation had a significant effect on the level of basic accounting understanding. Simultaneously (together) shows that the variables of emotional intelligence, learning behavior, and motivation affect the level of understanding of basic accounting. It can be concluded that motivation has a positive effect on the level of basic accounting understanding, while emotional intelligence has a negative effect on the level of basic accounting understanding and learning behavior has no effect on the level of basic accounting understanding. Students are expected to be able to balance emotional intelligence appropriately coupled with learning behavior that is in accordance with their respective abilities and always encourage themselves to always be enthusiastic and never give up in dealing with various things, especially in learning basic accounting concepts with various existing accounting problems to achieve the goal of understanding and good performance. Keywords: Basic Accounting Understanding Level, Emotional Intelligence, Learning Behavior, and Motivation